Strategi Positioning dan Citra Destinasi Objek Wisata Air Danau Sipin Jambi - Mohammad Ihsan; Garry Yuesa Rosyid; Ade Perdana Siregar (Universitas Batanghari, 2019)
Water tourism Danau Sipin Jambi is very potential to be done development, it is expected to grow a positive image on tourists visiting the water tourism Danau Sipin Jambi. The precise positioning strategy of the water tourism development of Danau Sipin Jambi positively impacts mainly in socio-economic. The purpose of the study are: (1) identifying influence between positioning strategies on visiting decisions; (2) Identify the influence between the positioning strategies on the destination image; (3) Identification of influences between the destination image and visiting decision; (4) Identification of the destination image role capable of the influence of positioning strategy against the visiting decision. Population used is the community of Jambi city while the sample is a community of Jambi city that more than once visited Danau Sipin Jambi as much as 200 people. The data method uses path analysis. The results of the research are known that the positioning strategy provides a significant influence on the destination image, positioning strategy and destination image to give a significant influence on the visit decision and the image of the destination can be The influence of positioning strategies on visiting decisions